Pemanfaatan Peta Konsep untuk Meningkatkan Hasil Belajar Peseta Didik SD Negeri 5 Sembiran - Puja Astawa, I Gede Juli Agus (Pratyaksa: Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2025)
There are many factors that influence the achievement of educational goals, especially now that we have entered a new transition from the pandemic that is sweeping the world today. the need for adjustments for students in learning and the role of creative teachers in developing the learning process to help students in receiving material. to overcome the above problems, where the author uses the learning media “Mind Mapping” to make it easier for students to form a way of thinking on each material explained and connectivity between materials. The success of this study is evidenced by an increase in learning outcomes and student completeness presentations ranging from cycle I to cycle II, namely the average student learning outcomes increased by 9.4 and the percentage of student completeness increased by 28% in cycle I, and in cycle II the average student learning outcomes increased by 8.4 and the percentage of student completeness increased by 29%.